Low Demineralized Caseins to Replace Sodium Caseinate for Application in Whipped Creams - Khadija Florence Dabo; Christine Chèné; Sylvain Prevost; Anne-Laure Fameau; Romdhane Karoui (Foods)
Caseinate is commonly used in the dairy industry for its stabilizing properties. Its functionalities are largely due to its manufacturing process involving a high level of demineralization that induces casein precipitation. To address this, the researchers are looking for alternatives to respond to consumer demands for high-quality ingredients and increase efficiency. In the present study, we explored low demineralization (0–43%) that preserves the casein integrity to produce caseins that can substitute caseinate in whipping creams (WC). The physicochemical, structural, and functional properties of these caseins were evaluated to assess their viability as surface-active agents in blend-fat whipping cream. The results showed that a demineralization level over 43% significantly impacts the size, secondary structures (β-sheets, β-turns, and α-helices particularly), and surface hydrophobicity that favorably impact the emulsifying properties but diminish the foam stability. WC made with caseins demineralized at 0 and 13% provided stable foam, with the lowest emulsion stability at 0% of demineralization. Using demineralized caseins at 13% offers a sustainable alternative to caseinate in food products requiring stable foams as WCs without significantly altering other desired functionalities such as overrun and emulsion stability. Further research studies into optimizing the demineralization process and exploring applications in other food matrices are suggested.